Bergbausammlungen in Deutschland Eine Bestandsaufnahme - Farrenkopf, Michael; Siemer, Stefan (Veröffentlichungen aus dem Deutschen Bergbau-Museum Bochum, 2020)
For the first time, the publication reveals the full dimensions of the material remembrance culture devoted to coal mining. It focuses on the museum as preserver of an objective heritage and on the objects themselves. Individual studies on technological innovations are juxtaposed against survey presentations about the museumization of coal mining. The volume is completed by a comprehensive overview of museums and collections in Germany.